The Development of a Mobile Game while Exploring Traditional Malaysian Cuisine - Norressan, Siti; Norhanifah Murli (Applied Information Technology And Computer Science, 2025)
This project introduces a mobile game designed to popularize traditional Malaysian cuisine globally using WebGL platform. The game features a main menu with three buttons: Start, Level, and Shop. Users begin by choosing Start or Level, leading to the first level where they serve customers within a time limit shown by a patience bar. Failure to serve in time results in no tips, while success earns coins. Players must earn 1,000 coins in three minutes to unlock the next of sixteen levels, providing ongoing challenges. Coins can be spent on decorations to improve customer satisfaction and tips. Presented in English, the game aims to make Malaysian food more widely recognized, following the Game Development Life Cycle methodology for systematic development.